2008
DOI: 10.1016/j.jasms.2008.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of phosphorylated residues in peptide-peptide noncovalent complexes formation

Abstract: Electrospray mass spectrometry (ESI-MS) has become the tool of choice for the study of noncovalent complexes. Our previous work has highlighted the role of phosphorylated amino acid residues in the formation of noncovalent complexes through electrostatic interaction with arginine residues' guanidinium groups. In this study, we employ tandem mass spectrometry to investigate the gas-phase stability and dissociation pathways of these noncovalent complexes. The only difference in the three phosphopeptides tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…In all cases, the major dissociation pathway for the NCX is the disruption of the noncovalent bond formed by the interaction of the phosphate group with the Arg residues guanidinium group, resulting in the generation of ions corresponding to the intact epitopes 25-27 (figure 3a). An alternative pathway was observed for the noncovalent complexes between the A2AR and D2R/D4R epitopes in which the NCX complex is fragmented along the covalent bond between the oxygen from Ser and the phosphorus of the phosphate from the A2AR epitope 8,9 (figure 3b). Similar pathways have been previously observed for NCXs formed by Arg and phosphorylated amino acid residues 8,9,25-27 , In addition, this pathway was favored by 40% more in the nonphosphorylated epitopes compared to the phosphorylated ones 26,27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the major dissociation pathway for the NCX is the disruption of the noncovalent bond formed by the interaction of the phosphate group with the Arg residues guanidinium group, resulting in the generation of ions corresponding to the intact epitopes 25-27 (figure 3a). An alternative pathway was observed for the noncovalent complexes between the A2AR and D2R/D4R epitopes in which the NCX complex is fragmented along the covalent bond between the oxygen from Ser and the phosphorus of the phosphate from the A2AR epitope 8,9 (figure 3b). Similar pathways have been previously observed for NCXs formed by Arg and phosphorylated amino acid residues 8,9,25-27 , In addition, this pathway was favored by 40% more in the nonphosphorylated epitopes compared to the phosphorylated ones 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…An alternative pathway was observed for the noncovalent complexes between the A2AR and D2R/D4R epitopes in which the NCX complex is fragmented along the covalent bond between the oxygen from Ser and the phosphorus of the phosphate from the A2AR epitope 8,9 (figure 3b). Similar pathways have been previously observed for NCXs formed by Arg and phosphorylated amino acid residues 8,9,25-27 , In addition, this pathway was favored by 40% more in the nonphosphorylated epitopes compared to the phosphorylated ones 26,27 . The absence of the observation of this pathway in the NCXs between D1R and NMDAR-NR1 epitopes suggests that the electrostatic attraction between them are weaker compared to the other epitopes in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Such interactions have been considered to explain the stability of arginine-phosphopeptide ion clusters [46][47][48] but do not seem to play a role in isolated peptide ions in which the phosphate group is neutral. This is presumably due to the donor-acceptor nature of the neutral phosphate group, where the P = O oxygen atom serves as a p-electron donor in solvating acidic protons of the peptide groups, and the acidic P-OH protons are internally solvated by suitable electron donors from the peptide amide or carboxyl groups.…”
Section: Precursor Ion Structuresmentioning
confidence: 99%
“…In studies using synthetic peptides, it has been shown that these electrostatic interactions are particularly stable. Thus, the Arg-phosphate interaction is so stable that when using collision-induced dissociation, the noncovalent interactions between the Arg guanidinium groups and the phosphate group remain intact even though the covalent bond between the serine and phosphate breaks (16,(31)(32)(33).…”
Section: Role Of Casein Kinase 1/2-mediated Phosphorylation In the Qumentioning
confidence: 99%